Optimization of 3D printing and in vitro characterization of alginate/gelatin lattice and angular scaffolds for potential cardiac tissue engineering - Ketabat, Farinaz; Maris, Titouan; Duan, Xiaoman; Yazdanpanah, Zahra; Kelly, Michael E.; Badea, Ildiko; Chen, Xiongbiao (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Engineering cardiac tissue that mimics the hierarchical structure of cardiac tissue remains challenging, raising the need for developing novel methods capable of creating structures with high complexity. Three-dimensional (3D)-printing techniques are among promising methods for engineering complex tissue constructs with high precision. By means of 3D printing, this study aims to develop cardiac constructs with a novel angular structure mimicking cardiac architecture from alginate (Alg) and gelatin (Gel) composite. The 3D-printing conditions were optimized and the structures were characterized in vitro, with human umbilical vein endothelial cells (HUVECs) and cardiomyocytes (H9c2 cells), for potential cardiac tissue engineering. Methods: We synthesized the composites of alginate (Alg) and gelatin (Gel) with varying concentrations and examined their cytotoxicity with both H9c2 cells and HUVECs, as well as their printability for creating 3D structures of varying fibre orientations (angular design). The 3D-printed structures were characterized in terms of morphology by both scanning electron microscopy (SEM) and synchrotron radiation propagation-based imaging computed tomography (SR-PBI-CT), and elastic modulus, swelling percentage, and mass loss percentage as well. The cell viability studies were conducted via measuring the metabolic activity of the live cells with MTT assay and visualizing the cells with live/dead assay kit. Results: Among the examined composite groups of Alg and Gel, two combinations with ratios of 2 to 1 and 3 to 1 (termed as Alg2Gel1 and Alg3Gel1) showed the highest cell survival; they accordingly were used to fabricate two different structures: a novel angular and a conventional lattice structure. Scaffolds made of Alg3Gel1 showed higher elastic modulus, lower swelling percentage percentage, less mass loss, and higher cell survival compared to that of Alg2Gel1. Although the viability of H9c2 cells and HUVECs on all scaffolds composed of Alg3Gel1was above 99%, the group of the constructs with the angular design maintained significantly more viable cells compared to other investigated groups. Conclusions: The group of angular 3D-ptinted constructs has illustrated promising properties for cardiac tissue engineering by providing high cell viability for both endothelial and cardiac cells, high mechanical strength, and appropriate swelling as well as degradation properties during 21 days of incubation at physiological conditions.